2004
DOI: 10.1093/jn/134.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Responsive to Intracellular Zinc Depletion in the Human Colon Adenocarcinoma Cell Line HT-29

Abstract: Zinc is essential for the structural and functional integrity of cells and plays a pivotal role in the control of gene expression. To identify genes with altered mRNA expression level after zinc depletion, we employed oligonucleotide arrays with approximately 10,000 targets and used the human colon adenocarcinoma epithelial cell line HT-29 as a model. A low intracellular zinc concentration caused alterations in the steady-state mRNA levels of 309 genes at a threshold factor of 2.0. Northern blot analysis and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 40 publications
(43 reference statements)
3
35
0
Order By: Relevance
“…By contrast, we have found that excess dietary zinc has minimal effects on Zip4 mRNA (7). It has been demonstrated that elevated zinc in cells leads to posttranslational processing, endocytosis of plasma membrane-localized Zip4, and degradation or ubiquitination (14). Those findings agree with our results on ZIP4 protein induction and that such degradative pathways are negligible during zinc-limited conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By contrast, we have found that excess dietary zinc has minimal effects on Zip4 mRNA (7). It has been demonstrated that elevated zinc in cells leads to posttranslational processing, endocytosis of plasma membrane-localized Zip4, and degradation or ubiquitination (14). Those findings agree with our results on ZIP4 protein induction and that such degradative pathways are negligible during zinc-limited conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly relevant to our present findings are the experiments reported by Kindermann et al (13,14) that demonstrated the marked upregulation of Klf4 by zinc chelation with TPEN in a human colon carcinoma cell line (HT-29). They suggested that the metal-responsive transcription factor MTF-1 was involved in regulation of Klf4 expression, since the human KLF4 promoter has MRE sequences upstream in the 65 Zn (57,000 cpm/ml) without DTPA and incubated for up to 60 min at 37°C.…”
Section: Discussionsupporting
confidence: 70%
“…Although labile zinc has been shown to be involved in several cellular pathways related to the regulation of cell fate, these mechanisms are not well characterized (3). Reduction of intracellular labile zinc has been associated with the induction of apoptosis, decreased cell proliferation, and altered cell cycle progression in a number of cancer cell types, including mammary adenocarcinoma (4), melanoma (5), colon adenocarcinoma (6), and lymphocytic leukemia (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of zinc-responsive gene regulation induced by intracellular labile zinc depletion in colon carcinoma HT-29 cells identified Krüppel-like factor 4 (KLF4, also known as GKLF) as one of the genes whose expression is most significantly changed (up-regulated) among >10,000 target genes tested (6). KLFs are members of the SP/XKLF family of transcription factors defined by an amino acid binding domain at the C termini that comprises three C2H2-type zinc fingers with similarity to the developmental gene Krüppel of Drosophila melanogaster (11).…”
Section: Introductionmentioning
confidence: 99%
“…concentrations Free intracellular zinc in Hep-2 cells treated with zinc as described above was monitored using microfluorometry of the zinc-specific dye Newport Green diacetate (6). Briefly, cells grown in black-bottom 96-well plates were incubated with Newport Green diacetate (5 μmol in PBS, dark, 30 min at 37 °C) and fluorescence intensity was determined by a multiplate reader TECAN SpectraFluor Plus (TECAN Austria GmbH, Grödig, Austria) at 485 and 535 nm, respectively with stable integration time 1000 ms and gain 150.…”
Section: Measurement Of Free Intracellular Zincmentioning
confidence: 99%